2021
DOI: 10.1371/journal.pone.0250628
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio in malignant pleural fluid: Prognostic significance

Abstract: Predicting survival of patients with malignant pleural effusions (MPEs) is notoriously difficult. A robust prognostic marker can guide clinical decision making. The neutrophil-to-lymphocyte ratio (NLR) in blood has been shown to predict survival in many cancers. Pleural fluid bathes the malignant pleural tissues, thus the NLR of the pleural fluid may reflect more closely the local tumour environment. The objective of this study was to explore the prognostic significance of pleural effusion NLR for MPE. We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
1
10
0
2
Order By: Relevance
“…Furthermore, the abundance of malignant mesothelioma patients in our study, which is known by its short life expectancy (12-21 months), with a median overall survival of about 15 months, rendering it one of the worst tumors as regard prognosis 21 , makes our results parallel to those of a recent study with 117 (MPE) patients which exposed that NLR (>0.745) in malignant pleural fluid was indicative to unfavorable prognosis. 22 Finally, in our work we found that the mean hematological (NLR) was significantly lower in (TPE) group compared with other groups. At the same time, this ratio was significantly lower in (MPE) group versus (PPE) group.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, the abundance of malignant mesothelioma patients in our study, which is known by its short life expectancy (12-21 months), with a median overall survival of about 15 months, rendering it one of the worst tumors as regard prognosis 21 , makes our results parallel to those of a recent study with 117 (MPE) patients which exposed that NLR (>0.745) in malignant pleural fluid was indicative to unfavorable prognosis. 22 Finally, in our work we found that the mean hematological (NLR) was significantly lower in (TPE) group compared with other groups. At the same time, this ratio was significantly lower in (MPE) group versus (PPE) group.…”
Section: Discussionsupporting
confidence: 51%
“…Although a number of studies have looked at pleural fluid biochemical parameters for prognostication of malignancy, few have investigated pleural fluid lymphocyte predominance in MPM. A recent study by Popowicz and colleagues found that in malignant effusions of all types (n = 117) a higher ratio of lymphocytes to neutrophils was associated with improved survival, although the study protocol did not specify that the sample needed to be collected at the time of diagnosis [ 10 ]. In our study we found that where the pleural fluid predominance was calculable this was an independent prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Natalia's study found that it is the increased neutrophils rather than decreased lymphocytes that drive the predictive value of NLR. [35]. Neutrophils play a critical role in the metastasis of cancer cells [36,37].…”
Section: Discussionmentioning
confidence: 99%